Associations of Caregiving Knowledge and Skills With Caregiver Burden, Psychological Well-Being, and Coping Styles Among Primary Family Caregivers of People Living With Schizophrenia in China - Zhou, Zonglei; Wang, Yao; Feng, Ping; Li, Tongxin; Tebes, Jacob Kraemer; Luan, Rongsheng; Yu, Yu (Frontiers in Psychiatry, 2021)
Background: There is a lack of clarity regarding the correlation of caregiving knowledge and skills with caregiving experiences of people living with schizophrenia (PLS). To address this gap, this comprehensive study examines the relationships of caregiving knowledge and skills to the primary family caregiver’s experiences of burden, psychological well-being (stress, anxiety, depression, caregiving rewarding feelings), and coping styles in China. Methods: A total of 395 primary family caregivers of PLS were enrolled in a cross-sectional study between May 2019 to September 2019. Each family caregiver was independently assessed on caregiving knowledge and skills, caregiver burden, psychological well-being, as well as coping styles. Results: A higher level of caregiving knowledge and skills was positively correlated with less stress (b = -0.48, P < 0.001), anxiety (b = -0.23, P = 0.029), depression (b = -0.29, P = 0.013) and more caregiving rewarding feelings (b = 0.54, P < 0.001). Also, caregivers with more knowledge and skills were more inclined to adopt positive coping strategies (b = 0.44, P < 0.001). Despite these differences, caregivers with different levels of caregiving knowledge and skills reported comparable caregiver burden (b = 0.11, P = 0.705) and the use of a passive coping style (b = 0.10, P = 0.169). Conclusion: Caregiving knowledge and skills is a reliable predictor of psychological well-being and active coping among the primary family caregivers of PLS. These findings inform the development of psychoeducational interventions to support family caregivers of PLS. Keywords: schizophrenia, primary family caregivers, caregiving knowledge and skills, caregiver burden, psychological well-being, coping styles